Management of Pregnancies With Cervical Shortening: A Very Short Cervix Is a Very Big Problem - Lee, Hee Joong (MedReviews, LLC, 2009)
Preterm birth (PTB), defined as birth before 37 weeks of gestation, is the leading cause of perinatal morbidity and mortality. PTB is a major cause of long-term health problems in neonates, including respiratory distress syndrome, chronic lung disease (bronchopulmonary dysplasia), infection, intraventricular hemorrhage, and severe neurologic deficit. In the absence of reliable clinical predictors of PTB, obstetric care providers should focus their attention on the 2 best and most widely accepted methods of identifying women at high risk of PTB in both nullipara and multipara: fetal fibronectin and cervical length measurements.